HUBUNGAN ANGGARAN PARTISIPASI, KECUKUPAN ANGGARAN, KOMITMEN ORGANISASI, MOIWASI DAN KINERJA MANAJERIAL DENGAN MODEL PERSAMAAN STRUKTURAL - Mohamad Nasir (Media Riset Akuntansi, Auditing & Informasi, 2009)
This research objective is to study the effect of budget adequacy, organizational commitment, and motivation on the relationship between budget participation and managerial performance. Data collection used 201 respondents that managers participate in preparing budget in public listed in Indonesia.and its' colleted by using questionnaire. Data analyzed by using structural equation model. This study found that budget participation have positive influenced on budget adequacy, but negative influence on organizational commitment. Budget participation have positive influenced on motivation but not significant. Budget participation have positive influenced on managerial performance. Budget adequacy have negative on managerial performance. Organizational commitment have positive influenced on managerial performance. Motivation have positive influenced on managerial performance. Budget participation influences on managerial performance directly more significant than through budget adequacy, organizational commitment, and motivation. The future research suggests it can be used by measurement model.Keywords: budget participation, budget adequacy, organizational commitment, motivation, managerial performance, structural equation model.